Holding big Pharma Accountable - Richard M Fleming1; Matthew R Fleming1; Tapan K Chaudhuri2 (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2019)
Recently Big Pharma has been in the news for increased costs associated with insulin and the opioid epidemic and the consequential costs associated with human suffering and loss of life. While these investigations and the holding of Big Pharma accountable have taken many years (in fact many decades), it did not occur until there was suffi cient public outrage and a considerable economic impact on an already strained medical and insurance system. Over the last several weeks the FBI has raided offi ces at uBiome where questionable billing practices for testing have been brought to light. On social media the general public has been reassured by uBiome that insurance will cover the costs of these tests. Also during the last few weeks, the U.S. Federal Government has disclosed new investigations of pharmaceutical companies who have been involved in potential "price fi xing" of generic drugs, dramatically controlling the costs of medications, which so many people depend upon.